2022
DOI: 10.1111/appy.12510
|View full text |Cite
|
Sign up to set email alerts
|

Piloting online training in the Pacific‐Ophelia project for child and adolescent mental health

Abstract: Introduction In June 2020, St Vincent's Mental Health, Fiji National University, and the Royal Australian and New Zealand College of Psychiatrists, Faculty of Child and Adolescent Psychiatry collaborated to deliver online, specialized child and adolescent mental health (CAMH) training to Pacific‐based healthcare workers. This accompanying research aimed to understand the telehealth model and structures that would sustain an engaged community of practice and support the development of professional networks acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As in previous studies the need for rural and Indigenous cultural contexts was highlighted. Chang et al 31 reported findings from their study of a telehealth model seeking to build a community of practice and grow professional networks in the Pacific region. This mixed method study of 43 A decline in the number of lay people and GPs using the service…”
Section: Telehealthmentioning
confidence: 99%
“…As in previous studies the need for rural and Indigenous cultural contexts was highlighted. Chang et al 31 reported findings from their study of a telehealth model seeking to build a community of practice and grow professional networks in the Pacific region. This mixed method study of 43 A decline in the number of lay people and GPs using the service…”
Section: Telehealthmentioning
confidence: 99%
“…The potential of telehealth for international engagement is immense although its full benefits and limitations are yet to be distilled. In 2020, a partnership involving Fiji National University (FNU), St Vincent's Mental Health and FCAP, pivoted to deliver a 12‐week CAMH lunch time professional development course via telehealth ( OPHELIA Training: Online Pacific Health Exchange; Chang et al 2022 ) . The biannual FCAP Pasifika Study Group (PSG) (Robertson, Hagali, et al, 2019 ) occurred online in September 2021 for the first time.…”
mentioning
confidence: 99%